2020
DOI: 10.1186/s12916-020-01562-5
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty versus non-surgical management for nasal obstruction in adults with a deviated septum: economic evaluation alongside a randomized controlled trial

Abstract: Background: For years, the benefits of septoplasty have been questioned. Due to the scarce and inconclusive literature, several National Health Service (NHS) Clinical Commissioning Groups in England decided to add septal surgery to their list of restricted procedures with low clinical value. Recently, evidence was obtained that septoplasty is actually more effective than non-surgical management for nasal obstruction in adults with a deviated septum. However, the relation between costs and effects of septoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…58 Moreover, in 2020, the same group published an economic evaluation showing that surgery would appear to be cost effective in the long term when compared to medical treatment. 59 The main strength of our study is that this is the first meta-analysis to answer the call for further research in investigating the efficacy of functional septoplasty, which has been voiced from clinical practice. However, this study is subjected to some limitations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…58 Moreover, in 2020, the same group published an economic evaluation showing that surgery would appear to be cost effective in the long term when compared to medical treatment. 59 The main strength of our study is that this is the first meta-analysis to answer the call for further research in investigating the efficacy of functional septoplasty, which has been voiced from clinical practice. However, this study is subjected to some limitations.…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that septoplasty is more effective than non‐surgical management for nasal obstruction in adults with a deviated septum 58 . Moreover, in 2020, the same group published an economic evaluation showing that surgery would appear to be cost effective in the long term when compared to medical treatment 59 …”
Section: Discussionmentioning
confidence: 99%
“…30 Five additional studies reported both short and long-term subjective outcomes but did not report p-values. 10,11,27,31,32…”
Section: Subjective Outcomesmentioning
confidence: 99%
“…Ten studies reported patient satisfaction as a percentage of patients, 13,[33][34][35][36][37][38][39][40][41] ten studies reported subjective symptom improvement as a percentage of patients, 14,15,32,[42][43][44][45][46][47][48] and three studies reported symptom improvement defined as a "clinically significant" change in NOSE or SNOT-22 score as a percentage of patients (Table IV). 10,49,50 Of the 3,113 patients included in these 23 studies, 2,348 (75.4%) reported satisfaction and/or improvement from preoperative baseline at their latest postoperative follow-up, which averaged 27.0 months. 10,[13][14][15][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Of these 3,11...…”
Section: Patient Satisfaction and Symptom Improvement Percentagesmentioning
confidence: 99%
See 1 more Smart Citation